2022
DOI: 10.7759/cureus.31369
|View full text |Cite
|
Sign up to set email alerts
|

Asthma and Its Impact on Pediatric Patients Undergoing Surgical Management of Tibial Shaft Fractures

Abstract: IntroductionTibial shaft fractures are a common presenting injury among the pediatric population. Asthma is also a common diagnosis that is frequently encountered in this population and has a significant impact on healthcare utilization, quality of life, and mortality. Given the high prevalence of these conditions and risks of peri-anesthetic respiratory complications, the purpose of this study was to evaluate an association between asthma and the incidence of 30-day postoperative complications following the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Using the National Surgical Quality Improvement Program Pediatric Participant Use Data File (NSQIP-P PUF), Krishna et al found that the risk of developing postoperative pneumonia within 30 days of inpatient pediatric surgery was almost double in children with asthma compared to those without [ 30 ]. Likewise, Tveit et al showed that children with asthma had nearly 6 times the risk of prolonged hospital stay following surgical management of tibial shaft fractures [ 31 ].…”
Section: Pre-hospital Racial Disparities and Their Influence On Surgi...mentioning
confidence: 99%
“…Using the National Surgical Quality Improvement Program Pediatric Participant Use Data File (NSQIP-P PUF), Krishna et al found that the risk of developing postoperative pneumonia within 30 days of inpatient pediatric surgery was almost double in children with asthma compared to those without [ 30 ]. Likewise, Tveit et al showed that children with asthma had nearly 6 times the risk of prolonged hospital stay following surgical management of tibial shaft fractures [ 31 ].…”
Section: Pre-hospital Racial Disparities and Their Influence On Surgi...mentioning
confidence: 99%